2013
DOI: 10.1177/0300985813493913
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Morphologic, and Immunohistochemical Features of Canine Orbital Hibernomas

Abstract: Hibernomas are uncommon benign tumors of brown fat that occur in humans and various animal species. They have not been observed in the orbit of dogs, humans, or other animals. Here we report clinical, light and electron microscopic, and immunohistochemical features of a series of 7 hibernomas arising in the orbital region of dogs. These neoplasms occurred in adult dogs with no breed predilection. The mean age of the affected dogs was 10.4 years (range, 8-13 years). All neoplasms presented as soft lobular masse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
5
26
0
Order By: Relevance
“…This study suggested that UCP1 expression distinguishes hibernomas from other lipomatous tumors; however, the study did not include a liposarcoma control group, and the expression of UCP1 by canine liposarcoma is unknown. 25 There is potential for misdiagnosis of benign hibernomas if the diagnosis is solely based on UCP1 expression, and this is prognostically significant as liposarcoma has potential for aggressive behavior both locally and systemically. The purpose of this study was to determine the immunohistochemical profile of canine liposarcoma in relation to markers classically associated with skeletal muscle and brown adipose differentiation.…”
mentioning
confidence: 99%
“…This study suggested that UCP1 expression distinguishes hibernomas from other lipomatous tumors; however, the study did not include a liposarcoma control group, and the expression of UCP1 by canine liposarcoma is unknown. 25 There is potential for misdiagnosis of benign hibernomas if the diagnosis is solely based on UCP1 expression, and this is prognostically significant as liposarcoma has potential for aggressive behavior both locally and systemically. The purpose of this study was to determine the immunohistochemical profile of canine liposarcoma in relation to markers classically associated with skeletal muscle and brown adipose differentiation.…”
mentioning
confidence: 99%
“…Hibernoma is an uncommon, benign soft tissue tumor, and so far has been reported in human beings [5][6][7] , rats [8,9] and dogs [10][11][12][13] . Hibernoma is thought to have derived from residual brown fat tissues which are most frequently found in the periscapular and interscapular region, the neck, axilla and shoulder, thorax, retroperitoneum and less frequently in thigh, popliteal fossa, buttock, intracranial sites [1] and breast [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, brown fat tissue has been demonstrated in interscapular, perirenal, and caudal subcutaneous adipose depots of adult cats [17] . On the other hand, hibernomas have been documented in varying locations in rats [8] and in dogs, they have been documented in corneum [12] , subcorneum [13] and omentum [10,11] . In this case report, hibernoma was diagnosed in the abdominal wall and showed adhesion to the mesenteric margin of the colon descendens.…”
Section: Discussionmentioning
confidence: 99%
“…Uncoupling protein‐1 immunoreactivity was documented, confirming the tissue of origin to be brown fat, consistent with a hibernoma . Specificity of UCP‐1 has been demonstrated in a case series of canine hibernomas and also confirmed by electron microscopy . Also confirming the diagnosis, no immunoreactivity to MyoD1 or myogenin was present.…”
Section: Discussionmentioning
confidence: 99%
“…Our case report details the clinical progression of a subconjunctival hibernoma and 14 months follow‐up following surgical excision. Clinical presentation and follow‐up were not available in the canine case series of 7 dogs . A case report by Ochoa in 1972 documented the presence of an abdominal hibernoma in a 9‐month‐old Labrador Retriever found incidentally during an exploratory laparotomy.…”
Section: Discussionmentioning
confidence: 99%